Perceived Risks and Evolving Travel Expectations: The Reimagining of Langkawi and Bali Tourism Landscapes after COVID-19 - Azrul Abdullah; Azila Azmi; Norshamshina Mat Isa; Putu Sucita Yanthy; Tinus Lis Indrinanto (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
The COVID-19 pandemic has profoundly impacted global tourism, altering travel behaviours and reshaping risk perceptions. This study investigates tourists' perceived risks and travel expectations in the new normal, focusing on Langkawi Island, Malaysia, and Bali, Indonesia, the two prominent Southeast Asian destinations. Using a qualitative approach, in-depth interviews with 60 participants (30 from each destination) revealed three key themes: destination risk, physical equipment risk, and vacation risk. The findings highlight the critical role of health and safety measures, including sanitation practices and digital innovations, in rebuilding tourist confidence. While Langkawi emphasizes family-friendly attractions and local travel bubbles, Bali leverages its cultural heritage and wellness tourism to align with evolving traveller priorities. Recommendations include adopting sustainable tourism practices, enhancing health communication, and integrating contactless technologies to foster resilience in the tourism sector. These insights offer valuable guidance for policymakers and stakeholders in designing adaptive strategies to ensure sustainable growth and competitiveness in the post-pandemic era.